The cinematography of gold paper (金纸) - Tan, Vanessa (Nanyang Technological University, 2020)
This creative work is a report on the art of cinematography in the film Gold Paper (金纸). It explains my intentions as it’s cinematographer from the development stage (pre-production) all the way to achieving the final look (production and post-production). I aim to portray a clear visual style through the key elements of cinematography: camera movement, lighting and colour theory. By employing these factors, I am able to use visual language to bring the film’s underlying themes and ideas to light, conveying the story and message that the director envisioned.